Efetividade do acompanhamento telefônico no estilo de vida de pessoas vivendo com HIV - Pedrosa, Samyla Citó (2018)
This study aimed to assess the effectiveness of a telephone follow-up on the lifestyle of people living with HIV. This is a multi-method study, consisting of a methodological research and a quasi-experimental study. The methodological research consisted of the construction and validation of a script for telephone follow-up. In the quasi-experimental stage, it was conducted an intervention to the lifestyle of people living with HIV. Data collection was carried out in two Specialized Attention Services for HIV/aids in Fortaleza, Ceará, from August 2016 to July 2017. The sample consisted of 118 people living with HIV, 65 comprising the control group (CG), receiving routine care according to the institution's protocol. Others (n = 53) were included in the intervention group (GI) and received telephone calls, in addition to routine care. The clinical trial was divided in two moments: 1) recruitment (T1), also named baseline, and 2) assessment of the outcomes (T2). Three instruments were used for data collection: Form of sociodemographic characterization and life habits of people with HIV; Individual Lifestyle Profile assessment tool; Satisfaction Scale for Management of Automated Disease by Telephone. The telephone follow-up lasted 18 weeks, during this period, biweekly calls were made, a total of ten calls for each participant. Each call had a main topic to be addressed, namely: presentation of telephone follow-up; adherence to ART; eating habits; physical activity; social support; self esteem; anxiety and depression; practice of preventive behaviour, sexuality and finalization. Data was analyzed using the Statistical Package for the Social Sciences (SPSS), version 24.0. Analysis of the construction and validation of the script for telephone follow-up was carried out from the calculation of Content Validation Index (CVI). Absolute and relative frequencies of continuous and categorical variables were calculated, Fisher's test was used to evaluate homogeneity among GC and GI. Generalized Linear Models technique was used to investigate the effects of telephone follow-up on lifestyle components. The script was validated by 11 nurses with expertise in the subject. All items in the script presented a CVI related to the degree of relevance above 0.90 (I-ICVI = 1; S-CVI / AVE = 1; S-CVI = 1). The groups were homogeneous regarding socio-demographic characteristics, lifestyle habits and lifestyle components. Statistically significant difference was observed only between sex (p = 0.042) and participants' age (p = 0.050). After the intervention, eating habits were statistically more adequate in the GI, when the effect of time (p = 0.024) and group (p = 0.047) were analyzed. Participants demonstrated high acceptability regarding telephone follow-up (94.3%). It is concluded that, although telephone follow-up did not demonstrate statistically significant change related to lifestyle components, it is considered viable for the care of people living with HIV since it favoured the proximity and support needed to reach a healthy lifestyle.